Nanoarchitectured Array Electrodes for Rechargeable Lithium‐ and Sodium‐Ion Batteries. Issue 10 (1st March 2016) - Xu, Yang; Zhou, Min; Lei, Yong
Abstract : Rechargeable ion batteries have contributed immensely to shaping the modern world and been seriously considered for the efficient storage and utilization of intermittent renewable energies. To fulfill their potential in the future market, superior battery performance of high capacity, great rate capability, and long lifespan is undoubtedly required. In the past decade, along with discovering new electrode materials, the focus has been shifting more and more toward rational electrode designs because the performance is intimately connected to the electrode architectures, particularly their designs at the nanoscale that can alleviate the reliance on the materials' intrinsic nature. The utilization of nanoarchitectured arrays in the design of electrodes has been proven to significantly improve the battery performance. A comprehensive summary of the structural features and fabrications of the nanoarchitectured array electrodes is provided, and some of the latest achievements in the area of both lithium‐ and sodium‐ion batteries are highlighted. Finally, future challenges and opportunities that would allow further development of such advanced electrode configuration are discussed. Abstract : A nanoarchitectured array is highlighted as an advanced electrode design for rechargeable lithium‐ and sodium‐ion batteries. Nanoarchitectured array electrodes provide a rapid ion diffusion route, directional electron transport pathway, large surface area, high structural stability, as well as composition advantages, and thus significantly improve battery performances and hold promise for other possible energy storage technologies.